Orange peel silage pre-dried and their use in ruminant feed – Review (Revista de Ciências Agroveterinárias, 2016)
The orange peel, consisting of bark, seeds and pulp, is a by-product of adequate nutritional value for feeding to ruminants, as it has nutritional characteristics, such as energy and similar protein to corn, this byproduct is widely used in the Brazilian livestock, under the pelletized form, the pelletizing being an expensive process, generating interest in fruit processing companies to develop markets for moist orange peel. However being a high moisture food, it deteriates in a short time and silage is emerging as an alternative to the storage of this by-product without compromising the nutritional characteristics. The orange peel is rich in pectin, highly degradable carbohydrate in the rumen which has a tendency to keep the rumen pH higher compared to traditional energy foods, which are rich in starch. This review aims to address issues regarding the silage of orange peel and their use in ruminant feed.
Keywords: Orange; pectin; byproduct.